A Comparison Between Pee Wee and Bantam Youth Ice Hockey Brain Trauma Profiles - Chen, Wesley (Université d'Ottawa / University of Ottawa, 2018)
There is an increasing concern surrounding brain trauma risks for young athletes participating in contact sports, as brain injuries in youth have detrimental consequences on their cognition, behaviour, and learning abilities (Ayr et al., 2009; Yeates and Taylor, 2005). Given the potential for future neurological and mental health issues, there is further need to quantify brain trauma within youth sport populations (Daneshvar et al., 2011). Ice hockey is a sport with high rates of brain injury in youth, and the shift from Pee Wee (ages 11-12) to Bantam (ages 13-14) hockey is an important transition period in which athletes are introduced to body checking (Black et al., 2017; Marar et al., 2012). The purpose of this study was to compare the brain trauma profiles between Pee Wee and Bantam hockey in terms of the head dynamic response, brain tissue deformation, and frequency of head impact events. Head impact events from 16 Pee Wee and 16 Bantam hockey games were analyzed, and 71 exemplar impact reconstructions were conducted. No differences were found between Pee Wee and Bantam for magnitudes of peak linear acceleration, peak rotational acceleration, or maximum principal strain (MPS). Overall frequency of head impact events was also similar between the two groups. However, chi-squared tests found that the type of head impact event was significantly associated with the age group (X2 (6) = 17.699, p = 0.006, φc = .347). Ice and boards head impact events were more frequent in Pee Wee, while shoulder and glass head impact events were more frequent in Bantam. There were slightly higher frequencies of events ≥26% MPS reported in Pee Wee. However, events were more frequently within the 17-25.9% MPS range for Bantam and were typically the result of shoulder to head impacts. While head impact events at younger ages are more accidental in nature, deliberate player contact from body checking is associated with greater risks for sustaining brain trauma. Policymakers should consider whether Bantam is the most appropriate age to continue allowing for body checking. Developing age-specific helmet technology may be an effective method for protecting against the unique brain trauma risks which are associated with different levels of youth hockey competition. Understanding the characteristics of how brain trauma occurs within youth hockey can help inform and guide future protective and preventative strategies to keep participation in this sport safe for all athletes.
Keywords: Brain; Trauma; Youth; Hockey; Concussion